LEMBAGA PERADILAN DALAM PERSPEKTIF PEMBARUAN HUKUM - Hoesein, Zainal Arifin (Jurnal Media Hukum, 2013)
The study aims at knowing the judicial power in legal reform perspective. In principle the rule of law, all public policy and election of public officials must be based on the rule of law. To realize the principle of supremacy of law, then one major factor is the presence of the judiciary is the embodiment of judicial power is independent, and authoritative. Law enforcement can not be regarded merely as a process of applying the law, however, has a broader dimension especially with regard to the dimensions of human behavior. The legal problems that will always stand out is the problem of